Virtual Impedances Optimization to Enhance Microgrid Small-Signal Stability and Reactive Power Sharing - Bahram Pournazarian; S. Sajjad Seyedalipour; Matti Lehtonen; Shamsodin Taheri; Edris Pouresmaeil (IEEE Access, 2020)
Microgrid instability poses critical issues to the power delivery following a load change or a tripping event. In island operating mode lack of grid intensifies this challenge. This study aims at controlling several converter-based distributed generations (DG) sharing the power in an island microgrid (MG). At first, the microgrid model including virtual impedances and phase-locked loop (PLL) is introduced. Afterwards a novel small-signal stability analysis for island microgrids is proposed. Finally, an optimization algorithm based on particle swarm optimization (PSO) is proposed to design the virtual impedances. The optimization algorithm analyzes all possible operating points and aims at maximizing the microgrid stability index while keeping the reactive power mismatches at minimum level. The fractional objective function facilitates reaching at these objectives simultaneously. The proposed optimization algorithm is implemented in two separate case-studies and the corresponding virtual impedances are drawn in any microgrid. On the other hand, The voltage drops are checked as a condition in the optimization process. The results drawn from two separate case-studies verify that the proposed algorithm effectively maximizes the microgrid stability index and minimizes the reactive power mismatches.